Development and Validation of Spectrophotometric Method for Determination of Flurbiprofen in Bulk and Formulation - Yadav, Bindu (International Journal of Pharmaceutical & Biological Archive, 2015)
Development and Validation of Spectrophotometric Method for Determination of Flurbiprofen in Bulk and Formulation